Glyphosate herbicide induces changes in the growth pattern and somatic indices of crossbred red tilapia (O. niloticus × O. mossambicus) - Muhammad, Umar Abubakar; Yasid, Nur Adeela; Daud, Hassan Mohd; Shukor, Mohd Yunus (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The development of glyphosate-resistant genetically modified organisms (GMO) has increased the use of herbicide glyphosate by several magnitudes in recent years. It is now the most commonly used pesticide globally that affects aquatic habitats, especially fish. This study aims to add new knowledge on the effect of technical grade glyphosate on several toxicity parameters and to identify the most effective parameter in predicting technical grade glyphosate chronic toxicity (seven weeks) to fish, especially Malaysia’s heavily farmed red tilapia. The results show that a relatively high concentration of technical grade glyphosate is needed to induce significant changes in all tested parameters. However, the results also indicate that the bodyweight index is the most sensitive toxicity parameter in that a reduction in body weight was observed at 25 mg/L of glyphosate. Negative correlations between the glyphosate concentration and toxicity parameters such as specific growth rate (SGR), hepato-somatic index (HIS), and gonado-somatic index (GSI) were observed. The fish condition factor and feed conversion ratio were found not to be affected at the highest glyphosate concentration tested (150 mg/L). To conclude, crossbred red tilapia (O. niloticus × O. mossambicus) is one potential species for evaluating the toxic effects of technical grade glyphosate on fish.